Financial accounting + attack book - Libby, Robert (McGraw-Hill/Irwin, 2007)
Libby/Libby/Short wrote this text based on their belief that the subject of financial accounting is inherently interesting, but financial accounting textbooks are often not. They believe most financial accounting textbooks fail to demonstrate that accounting is an exciting field of study and one that is important to future careers in business. When writing this text, they considered career relevance as their guide when selecting material, and the need to engage the student as their guide to style, pedagogy, and design. Libby/Libby/Short is the only financial accounting text to successfully implement a real-world, single focus company approach in every chapter. Students and instructors have responded very favorably to the use of focus companies and the real-world financial statements. The companies chosen are engaging and the decision-making focus shows the relevance of financial accounting regardless of whether or not the student has chosen to major in accounting